(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2024)
Penile reimplantation is a surgical medical procedure that is used when we are faced with trauma where the penis has been severed, penile trauma is not frequent and is caused from its bibliographic etiology by sharp objects, trauma from traffic accidents, they can be unintentionally caused by the zipper of the pants closure, it can also be caused by firearms where the projectile accidentally reaches that delicate area. In addition to that, penile implants could also cause trauma due to misuse of these. Other not so common causes are iatrogenic, and trauma caused by bites and amputations from sexual assault. The case we are reporting is of a 53-year-old man of low sociocultural status who lives in the city of Guayaquil and who was transferred to the specialty hospital "Dr. Abel Gilbert Pontón" and treated in the Emergency for presenting amputation of the middle third of the penis due to a work accident due to a chainsaw. He also presented a sharp wound to the skin and subcutaneous cellular tissue on the left thigh, 10 cm in length, with intense blood loss, pain. Interconsultation with the Urology Department was carried out to proceed with direct penile reimplantation plus suprapubic cystostomy under general anesthesia. The repair was carried out in two stages, in the first stage anastomosis of the shaft of the penis was performed and using a probe as a guide, the union was performed with microsurgery and in the second stage macrosurgery was used, and suprapubic cystostomy to exert resistance to elasticity that allows better function.